Estudo iconológico das obras pictóricas de Aurélio de Figueiredo pertencentes a acervos da cidade de Manaus - Martinez, Keyla Morais da Silva (2018)
In the second half of the nineteenth century, many artists in transit held exhibitions in various places in Brazil. The predominant style of these productions was the neoclassical academicism that also had resonance in great part of the works of the artist Aurélio de Figueiredo. This study was dedicated to the iconological interpretation of the works of the artist that are present in collections of the city of Manaus. His biography was investigated through the survey of primary sources and a trace of his presence in the city was made. It was also analyzed the historical context of the production of the works, which was of great relevance to observe the political reflexes of the time in art, and to unveil symbolic of works. The works analyzed were: Princesa Isabel and Dom Pedro II, belonging to Instituto Geográfico e Histórico do Amazonas; A ilusão do Terceiro Reinado or O último baile da Ilha Fiscal and O Banho de Ceci, which are part of the collection of the Pinacoteca of the State of Amazonas and A Redenção do Amazonas, which belongs to the Public Library of the State of Amazonas. Keywords: Aurélio de Figueiredo, National History, Art in Amazonas.